Making Polyisoprene Self‐Healable through Microstructure Regulation by Rare‐Earth Catalysts - Wang, Haobing; Yang, Yang; Nishiura, Masayoshi; Hong, You‐lee; Nishiyama, Yusuke; Higaki, Yuji; Hou, Zhaomin (Angewandte Chemie International Edition, 2022)
The creation of self‐healing polymers from commodity olefins is of great interest and importance but has remained a challenge to date. We report here for the first time the synthesis of self‐healing polymers by catalyst‐controlled polymerization of a simple commodity diene, isoprene. We found that polyisoprenes having an appropriate mixture (ca. 70/30) of 3,4‐ and cis‐1,4‐microstructures synthesized by using a half‐sandwich scandium catalyst could act as excellent self‐healing elastomers without any external intervention. The unprecedented self‐healability could be ascribed to nanoscale heterogeneities formed by microphase separation of the relatively hard 3,4‐segments from a flexible cis‐1,4‐segment matrix. The hydrogenated polyisoprenes (without C=C bonds) with the analogous microstructures also exhibited excellent mechanical and self‐healing properties, further demonstrating that even simple polyolefins can be made self‐healable if the microstructures are appropriately regulated. Polyisoprenes with an appropriate mixture of 3,4‐ and cis‐1,4‐microstructures were synthesized by scandium catalyst‐controlled polymerization of isoprene. The polyisoprenes exhibited excellent elasticity and self‐healability without any external intervention, which is a result of microphase separation of the relatively hard 3,4‐segments from a highly flexible cis‐1,4‐segment matrix at the nanoscale.